(Di)triazolylidene manganese complexes in catalytic oxidation of alcohols to ketones and aldehydes. Issue 10 (1st May 2019) - Pinto, Mara F.; Olivares, Marta; Vivancos, Ángela; Guisado-Barrios, Gregorio; Albrecht, Martin; Royo, Beatriz
Abstract : A robust bimetallic manganese complex with a mesoionic 1, 2, 3, -triazolylidene ligand for efficient oxidation of alcohols with tert -butylhydroperoxide. Abstract : Carbonyl manganese complexes with chelating or bridging mesoionic di(1, 2, 3-triazolylidene) ligands were efficiently synthesised and fully characterised, including the X-ray diffraction study of a bimetallic manganese(0) complex. This unprecedented bimetallic complex displayed high yield and selectivity in the catalytic oxidation of secondary alcohols and benzyl alcohol with tert -butyl hydroperoxide under mild conditions.